miR-29 Family as Epigenetic Regulators of DNMTs in Prostate Cancer and Benign Prostatic Hyperplasia - Yudi Gebri Foenna; Nilüfer Şahin Calapoğlu; Okan Sancer; Muhammet Yusuf Tepebaşı; Mustafa Calapoğlu (The Indonesian Biomedical Journal, 2025)
BACKGROUND: The miR-29 family (miR-29a/b/c) is recognized as a tumor suppressor, directly targeting DNA methyltransferases (DNMTs), key regulators of epigenetic gene silencing. Even though miR-29 has been implicated in tumor progression, its regulatory interaction with DNMT3A/3B, particularly in prostate cancer (PCa), has not been elucidated well. This study was conducted to explore the potential of miR-29a/b/c in targeting DNMT3A/3B in PCa and benign prostatic hyperplasia (BPH), addressing a critical gap in understanding their epigenetic role.METHODS: This study used tissue samples that were taken surgically from 30 subjects that consisted of 15 diagnosed PCa and 15 BPH patients (as the control group), aged between 18-75 years, with urinary system disorders and had a prostate specific antigen (PSA) value between 1.18 and 56.15 ng/dL. The miR-29a/b/c and DNMT3A/3B expressions were measured using quantitative real-time PCR (qRT-PCR). The variations in mean values across groups, the associations between miR-29a/b/c and DNMT3A/3B expression levels parameters, as well as the correlation between miR-29 levels and DNMT3A/3B variables were then statistically analyzed.RESULTS: The expression levels of miR-29a/b/c were significantly downregulated in the PCa subjects compared to the BPH subjects (p<0.05), and negative correlations were observed between miR-29a/b/c and DNMT3A/3B in the PCa subjects (p<0.001). In addition, a significant inverse correlation was detected only between miR-29a and DNMT3B in BPH subjects (p<0.05).CONCLUSION: The results of this study indicated that miR-29a/b/c in PCa may act as a negative regulator directly targeting DNMT3A/3B. These findings support the role of miR-29s in developing miRNA-based strategies for treating PCa.KEYWORDS: prostate cancer, benign prostatic hyperplasia, epigenetic, DNA methyltransferases-3A/3B, miR-29a/b/c